Financial literacy education and retirement planning among civil servants in Johor / Shamsinar Rahman ... [et al.] - Rahman, Shamsinar; Safian, Norliana; Abdul Hadi, Khairul Anuar; Md Pauzi, Suria Fadhillah (2021)
Retirement is an important life event that everyone goes through, and a good retirement necessitates careful planning. With the growing number of senior people, the issue related to retirement has become increasingly important, and governments all over the world are prioritizing financial retirement planning (Selvadurai et al., 2018). However, retirement planning does not only become essential to the retirees but to other individuals too. Therefore, once start working, the employees must begin saving for retirement at a young age to take advantage of the time value of money (Universiti Putra Malaysia, 2018). It is because this will determine their financial status after working life. Thus, to have successful retirement planning, individuals must have vital financial literacy education. There have been numerous studies on financial literacy education and retirement planning readiness. For instance, a study conducted by Ringgit Plus reveals a lack of retirement planning among Malaysians. The study found that 60 percent of their respondents believe that their EPF savings only can last for ten years, while 70 percent believe that EPF saving is not enough for their retirement. Even though they have such fears yet almost 50 percent of the respondents still do not start any retirement planning (RinggitPlus, 2020). Thus, apart from excellent health and a joyful, meaningful life, the EPF board listed financial security as one of the three essential elements of a peaceful retirement (Tan & Singaravelloo, 2020). In addition, according to a 2017 survey done by Credit Counselling and Debt Management Agency (AKPK), 55 percent of 1000 Malaysian respondents may not be ready to retire due to financial concerns, with inadequate financial planning being blamed (Shah, 2017).